Consumers’ Perception of Firm responses to Corporate Social Responsibilities within the Luxury Fashion Industry - Asma Manzil Luquman, Affaan; Escobar Rios, Andrea; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The luxury fashion industry has seen an increase in the adoption of Corporate Social Responsibility (CSR) programs to improve brand image and attract socially conscious consumers. However, little is known about how women consumers perceive the CSR initiatives of luxury fashion brands and how their views and behaviors impact their purchasing decisions. This study aims to identify the key factors that influence women's perceptions of luxury fashion companies' CSR initiatives and to assess the effectiveness of various CSR practices from their perspective. Through a survey of women consumers, this study will provide insights into the strategies that luxury fashion companies can adopt to enhance their CSR efforts and improve brand perception. The research questions focus on identifying CSR practices in the luxury fashion industry, understanding the impact of CSR on women's perception of luxury fashion brands, and exploring strategies for companies to increase their commitment to CSR. The study is conducted for the luxury fashion industry and the practical part of the thesis is based on a CAWI questionnaire (quantitative questionnaire) to obtain responses from women consumers. Overall, this research aims to contribute to a deeper understanding of women consumers' perception of CSR in the luxury fashion industry.
Vedoucí práce: Andrea Escobar Rios
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses